2022
DOI: 10.3389/fonc.2022.1038678
|View full text |Cite
|
Sign up to set email alerts
|

Multiple colorectal adenomas in Lynch syndrome

Abstract: BackgroundLynch syndrome has not traditionally been considered to have a high colorectal adenoma burden. However, with increasing adenoma detection rates in the general population, the incidence of adenoma detection in Lynch syndrome may also be increasing and leading to higher cumulative adenoma counts.AimTo clarify the prevalence and clinical impact of multiple colorectal adenomas (MCRA) in Lynch syndrome.MethodsA retrospective review of patients with Lynch syndrome at our institution was performed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Elevated adenoma burden has been shown in about 6% of LS patients, and multiple cumulative adenomas are particularly observed in carriers of pathogenic MSH6 and PMS2 gene variants as well as individuals with CMMRD ( 8 , 34 , 35 ). Understanding the history of adenomas of LS patients is important as those with > 10 cumulative adenomas are much likelier to develop advanced neoplasia ( 8 , 34 ). Familial risk for tumor multiplicity has been proposed before and some polygenic factors have been identified ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated adenoma burden has been shown in about 6% of LS patients, and multiple cumulative adenomas are particularly observed in carriers of pathogenic MSH6 and PMS2 gene variants as well as individuals with CMMRD ( 8 , 34 , 35 ). Understanding the history of adenomas of LS patients is important as those with > 10 cumulative adenomas are much likelier to develop advanced neoplasia ( 8 , 34 ). Familial risk for tumor multiplicity has been proposed before and some polygenic factors have been identified ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Amsterdam criteria, used as an aid in the clinical diagnosis of LS, draws heavily on the family history of CRC, but additionally states the need for the absence of polyps to distinguish LS from familial adenomatous polyposis (FAP) (3,4). Although the cumulative lifetime adenoma burden of LS patients generally stays below ten, recent data has shown that LS may manifest with an elevated polyp count, and that individuals with pathogenic germline variants in different genes may undergo gene-specific tumorigenesis (5)(6)(7)(8)(9), creating difficulties for diagnosis. LS patients with an elevated adenoma count are additionally significantly more likely to have an advanced colorectal neoplasia (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation